2007
DOI: 10.1037/1076-8971.13.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for remediating juveniles' adjudicative incompetence.

Abstract: With the application of adjudicative competence requirements to adolescent defendants, there is a growing need for interventions to enhance the legal capacities of adolescents who are found to be incompetent. By reviewing developmental, clinical, and educational research, the authors discuss whether it is possible to enhance youths' legal capacities and, if so, what the most promising approaches may be. Psychoeducational interventions for youth are discussed, as well as the possibility of changing the demands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…For instance, the MacArthur Juvenile Adjudicative Competence study reported that approximately one-third of adolescents aged 11-13 and one-fifth of adolescents aged 14-15 had impairments in their legal understanding and/or their ability to reason about legal decisions (Grisso et al, 2003). Other studies have examined the characteristics of juvenile defendants referred for competence evaluations and restoration (e.g., Kruh, Sullivan, Ellis, Lexcen, & McClellan, 2006;McGaha, Otto, McClaren, & Petrila, 2001), approaches for assessing adolescents' competence (e.g., Christy, Douglas, Otto, & Petrila, 2004;Ryba, Cooper & Zapf, 2003), and strategies to improve adolescents' legal capacities (e.g., Cooper, 1997;Viljoen & Grisso, 2007).…”
mentioning
confidence: 98%
“…For instance, the MacArthur Juvenile Adjudicative Competence study reported that approximately one-third of adolescents aged 11-13 and one-fifth of adolescents aged 14-15 had impairments in their legal understanding and/or their ability to reason about legal decisions (Grisso et al, 2003). Other studies have examined the characteristics of juvenile defendants referred for competence evaluations and restoration (e.g., Kruh, Sullivan, Ellis, Lexcen, & McClellan, 2006;McGaha, Otto, McClaren, & Petrila, 2001), approaches for assessing adolescents' competence (e.g., Christy, Douglas, Otto, & Petrila, 2004;Ryba, Cooper & Zapf, 2003), and strategies to improve adolescents' legal capacities (e.g., Cooper, 1997;Viljoen & Grisso, 2007).…”
mentioning
confidence: 98%
“…While CST law sets the legal requirements for youth to be adjudicated in juvenile court, developmental psychology scholars argue that CST may be a paradox for most youth in juvenile court as they do not have the developmental capacities to effectively participate in their trials (Grisso et al, 2003). Research that focuses on mental health experts' CST evaluations finds that youth who are found incompetent are more likely to be of young age, have intellectual impairments, have a special education placement, and/or have a diagnosis of psychosis (Evans, 2003;Kruh, Sullivan, Ellis, Lexcen, & McClellan, 2006;Scott & Grisso, 2005; for a review, see Viljoen & Grisso, 2007). Some scholars argue for a lower standard of CST in juvenile court, as most youth below the age of 16 are significantly more impaired on competence standards (see Grisso et al, 2003); in particular, the threshold should be lower as in most cases, the punishment stakes are lower than those facing criminal defendants (Scott & Grisso, 2005).…”
Section: Psycho-legal Cst Researchmentioning
confidence: 98%
“…2006; Mumley et al. 2003; Scott and Grisso 2005; Viljoen and Grisso 2007). In Cooper’s (1997) study of delinquent youth ages 11–16 enrolled in their first institutional placement, she finds that CST is significantly related to age, but contrary to expectations, most children at all ages did not meet the assessment threshold to be considered competent to stand trial.…”
Section: Competency To Stand Trial: Pscho‐legal Literaturementioning
confidence: 99%
“…2001; Scott and Grisso 2005). Furthermore, attempts to restore youth to competence when the primary basis for his/her incompetence is maturational/developmental does not make sense since maturation cannot be taught or hurried (Scott and Grisso 2005; Viljoen and Grisso 2007).…”
Section: Competency To Stand Trial: Us Legal Doctrinementioning
confidence: 99%